Survey On Phytophthora Diseases In Nagpur Mandarin (Journal of Plant Disease Sciences, 2018)
Rapid roving survey was undertaken during 2015-2016 to assess the incidence and severity of gummosis and root rot caused by Phytophthora spp. in major citrus growing areas of Amravati district of Maharashtra during peak period of diseases i.e. July to December. Almost all surveyed orchards were found infected with Phytophthora spp. Three Phytophthora spp. i.e. Phytophthora palmivora, P. nicotianae = parasitica and P. citrophthora were associated with gummosis and root rot. Highest gummosis incidence of 50.50 percent observed in the village Perla field II, while highest disease intensity was recorded in the Lehgaon field II (28.00%) of Morshi tahsil. Similarly, highest root rot incidence observed in Sawarkhed field II (40.00%) with highest disease intensity was recorded in Perla field II (24.55%). Minimum incidence and intensity of gummosis was recorded in Manglurpeth field II which was 14.00 % and 8.50 %, respectively. Lowest disease incidence (18.00%) and intensity (6.70 %) of root rot was recorded in Manglurpeth field I. Citrus jambhiri Lush is the most widely used root stock for most of citrus scion in study area, which is highly susceptible to Phytophthora diseases.
Keywords: Survey; Phytophthora spp; incidence; intensity; gummosis; root rot